2013
DOI: 10.1016/j.phrp.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Completed Status and Seropositivity of Hepatitis A Immunization Among Children Aged 1–3 Years and 6–8 Years in South Korea

Abstract: This study was designed to identify factors associated with hepatitis A immunization status and seropositivity in Korean children. In-person interviews, reviewing their vaccination cards and testing hepatitis A antibody were conducted with 389 children aged 1–3 years and 544 children aged 6–8 years. In all age groups, earlier birth order was the only significant factor in children receiving either single or both doses of the vaccination. And completion of the second dose of vaccination was a prerequisite for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A recent nationwide study by Lee et al (2011) explored the change in HAV sero-epidemiology over 30 years in Korea and concluded that the most vulnerable population in 2008-2010 was those aged 20-29 years; this is in contrast to 30 years earlier, when children under 10 years of age were most at risk. In this review, increasing seropositivity in Korean 1-10-year-olds was also observedlikely a consequence of vaccine introductionfrom 26.8% in 1989 to 63.6% in 2011; this was accompanied by a decreasing seroprevalence in those aged 21-30 years, from 95% in 1989 to 18.8% in 2011 (Hong et al, 2013).…”
Section: Discussionmentioning
confidence: 77%
“…A recent nationwide study by Lee et al (2011) explored the change in HAV sero-epidemiology over 30 years in Korea and concluded that the most vulnerable population in 2008-2010 was those aged 20-29 years; this is in contrast to 30 years earlier, when children under 10 years of age were most at risk. In this review, increasing seropositivity in Korean 1-10-year-olds was also observedlikely a consequence of vaccine introductionfrom 26.8% in 1989 to 63.6% in 2011; this was accompanied by a decreasing seroprevalence in those aged 21-30 years, from 95% in 1989 to 18.8% in 2011 (Hong et al, 2013).…”
Section: Discussionmentioning
confidence: 77%